Implied choice of law agreement in international contracts against a previous express agreement - Regarding the Provincial Court of Barcelona (SAP Barcelona) resolution 756/2023 of 19th of May 2023 - Orbegozo Miguel, Xabier (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This paper is based on the analysis of a resolution of the Provincial Court of Barcelona referring to a contract for the sale of shares of a company incorporated in Romania between persons with habitual residence in Spain. That contract contained a choice of court agreement in favour of the Romanian courts, the law of the same State being chosen to govern the contract. Having obtained a first unfavourable decision in Romania, the plaintiff sued in Spain. This claim, which seeks the nullity of the contract, is based on Spanish law. We will analyse, on the one hand, the competence of the Spanish courts in this case, the possibility of applying a law that is not the one provided for in the contract and the possible difficulties in recognising this Spanish judgment in Romania.
Keywords: International contract; party autonomy; implied choice of law; Rome I Regulation; Brussels I Regulation-recast